As aprendizagens interativas e cognitivas em jogos tradicionais/populares nas aulas de educação física - Cruz, Rodrigo Wanderley de Sousa (2014)
This thesis aims to investigate the mode of action of the elementary school students of a public school, in traditional / popular games in physical education classes. In the face of being a study that addresses the game from a different perspective on their experience , rather than the play by play , we focus on the game as a facilitator of learning from its internal operating logic of the existential mood of the players, unfolding in possible cognitive advances .Thus, we have the following problem-question : What are the interactive and cognitive learning that occurs in traditional / popular opposition cooperation - lived classes of Physical Education games ? Given the relevance of this topic, we reveal our overall goal was to examine the interactive and cognitive learning in traditional / popular games experienced by students in physical education classes. The research is characterized as direct, descriptive and analytical character with qualitative data analysis, ethnographic and participant perspective. The subjects took twelve students enrolled YEAR 7 and regular attendance in physical education classes at Escola Municipal Augusto dos Anjos , located in the Cristo Redentor neighborhood in the city of João Pessoa, Paraíba . The instruments used for data collection were field diary and image planes, subsidized by the techniques of participant observation and dialogical group. We analyzed Shot and Bar -Flag games grounded by Praxiologia Motriz ( Parlebas , 2008; 2001; 1999 Existential - Analytic Movement ( Gomes-da-Silva , 2012.2011 , 2001) and Reciprocal Assimilation ( Piaget , 1994; 1990;1977) identified several adjustments in decision making of the players on the main actions in games: the pass and shot , mediated by relationships with other players , spaces and objects , generating new learning in cooperative relations - opposition in minimizing indifferently for the primary as well as in the transition from automatic to conduct active , ie , less repetitive and more inventive . conclude that learning in the traditional / popular games run relationships with other human and non-human , these endless exchanges of gestures , tactics , wraps and constant perceptions that , starting from an internal operating logic , one can gain new , more thoughtful , intelligent decisions on deploying new means of language and existential meanings in games lived in Physical Education classes.